IMPLEMENTASI UU NO. 41 TAHUN 1999 TENTANG KEHUTANAN (Penegakan Hukum Pada Tahap Penyidikan Terhadap Kasus Illegal Logging Di Polres Wonogiri) - SUPADI, SUPADI (Dinamika Hukum, 2015)
The purpose of this study is to examine and analyze the implementation of Law No. 41 Year 1999 on Forestry that law enforcement in the investigation phase of cases of illegal logging, as well as assess and explain the constraints faced by law enforcement in the investigation of cases of illegal logging in Police Winton Illegal logging (logging), all the people of Indonesia have been very familiar with this term. Every day discussed, even has always been a very hot topic amid the fundamental problems of this nation. Some claimed that illegal logging is a crime that is incalculable. This type of research used socio-juridical type of research, namely by reviewing the provisions of the applicable law and what happens in reality the community. The nature of descriptive analytical study. Will be analyzed descriptively object under study, in this case regarding the implementation of Law No. 41 Year 1999 on Forestry in law enforcement in the investigation stage of illegal logging cases. Results of research and discussion process interrogate suspected of committing criminal offenses in the field of forestry, especially illegal logging should be subject to the Act No. 41 of 1999 which also can not be separated from the clauses in the Code of Criminal Procedure (Code of Criminal Procedure) concerning the investigation and then apply the procedural law guided by the Code of Criminal Procedure. Investigators Civil Servant more active role in investigating the crime of illegal logging terhadp this always caused by the limitations faced by police investigators, particularly the limitations of personnel in the field investigators. In addition, lack of knowledge in a particular field causes the Police are not able to handle all criminal offenses that occur. Obstacles encountered in the implementation of criminal investigations forestry, among others, the lack of legislation regarding criminal acts, the infrastructure is still lacking, there is a lack of community participation in the implementation of criminal investigations of illegal logging, an area with a number of personnel INP is not balanced, there are many differences in perception between the communal land boundary commensurate with the State forest (rainforest), as well as the place or difficult terrain to be taken in carrying out criminal investigations of illegal logging. Keywords: Implementation, Law Enforcement, Investigation, Illegal Logging